Parasitoids and Predators as Biological Agents against White Stem Borer (Scirpophaga innotata) - Arum Dewi, Pervitara; Wahyuni, Srilah Nora; Ilwati, Uun; Akram, Ahdiatsa Hairi; Sarjan, M. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
One of the primary challenges in rice cultivation is the disturbance caused by pest infestations. Among the pests that frequently cause damage to rice plants is the white rice stem borer (Scirpophaga innotata). The life cycle of Scirpophaga innotata comprises egg, larva, pupa, and adult stages. This article is based on a literature review and discusses the natural enemies most commonly encountered at each stage of the Scirpophaga innotata life cycle. The findings of this article can be summarized as follows: Natural enemies of the white rice stem borer during the egg stage include parasitoids such as Trichogramma japonicum Ashm., Tetrastichus schoenobii, and Telenomus rowani, as well as the predator Conocephalus sp. During the larva-pupa stage, parasitoids such as Apantheles sp., Bracon sp., Tropobracon sp., and Temelucha bigutella are present, along with predators like Miscrapis crocea and Harmonia octomaculata. Regarding the adult stage, parasitoids were not found to be natural enemies of adult S. innotata. However, the most commonly encountered predators include Coccinella transversalis (Thunberg) and Paederus sp.